The afterlife of megastructures in the aftermath of mega-events: the case of Cape Town Stadium - Mwedzi, Alick (School of Architecture, Planning and Geomatics, 2018)
Large scale global spectacles such as the FIFA World Cup and the Olympic Games demand infrastructure of a suitably grand magnitude - the stadium being the centrepiece of this infrastructure. However, because the mentioned events are hosted in a different location each time they take place, the stadia they leave behind often face uncertain futures, as the events and capacity for which they are originally designed are difficult to maintain following the spectacle. The intention of this dissertation is to explore how adaptive reuse can be considered as an approach towards stadia in the aftermath of global mega-events. This exploration focuses on Cape Town Stadium, a venue for the 2010 FIFA World Cup hosted in South Africa. The dissertation engages Cape Town Stadium in terms of an exploration into understanding the nature of stadia as very large buildings, and the challenges and opportunities adaptive reuse presents to their continued use. Cape Town stadium is understood as a robust concrete structure with a high embodied energy and a variety of spatial and environmental conditions created by contrasting deep and shallow spaces, and different engagements with external environments. These conditions present a challenge to providing the spatial and environmental requirements of an alternative programme, especially where spaces are deep, isolated, inappropriately scaled or articulated by structure. Informed by Metabolist megastructure thought, adaptive reuse is explored in an approach that regards the existing as a robust permanent structure and introduces a secondary order of architecture: more delicate and less robust - that augments the existing structure to provide for the spatial and environmental requirements of a new programme - an educational campus - introduced to occupy the underutilised portion of the Stadium.